“Semester Marriages” and the Unintended Psycho-Social Challenges within Institutions of Higher Learning: Implications for Social Work Practice - Mafa, Itai Hlonie; Simango, Tapiwanashe G.; Chigangaidze, Robert Kudakwashe; Mudehwe, Elia (Qualitative Sociology Review, 2024)
The sexual economy prevalent within universities, as well as how young people perceive, interpret, and experience their sexuality, present complex dynamics, which, if not handled with great emotional intelligence, may disrupt their educational aspirations. This paper investigates the psycho-social implications of “semester marriages” within institutions of higher learning. Guided by principles of the qualitative approach and the theory of planned action, the paper disinterred that students experienced intense regret and guilt as a result of backstreet abortions. Soul-tie complications emanating from sharing the “wife-husband” bond also made it difficult for some students to move on after a breakup, leading to disruptions in their educational focus. In extreme cases, such an inability to deal with the adverse effects of “semester marriages” culminated in crimes of passion. The paper desists from pathologizing the “semester marriages” phenomenon and advocates for the strengthening of psycho-social support modalities within university settings to increase the accessibility and visibility of therapeutic services through a school social work model. Furthermore, universities, in partnership with other relevant stakeholders, are urged to prioritize sexual and reproductive education and services among the youth as provided for in the Constitution of Zimbabwe of 2013 to impart life skills that can equip students to make informed sexual and reproductive decisions.